The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.7554/elife.05075
|View full text |Cite
|
Sign up to set email alerts
|

Titles and abstracts of scientific reports ignore variation among species

Abstract: An analysis of more than 1000 research articles in biology reveals that the name of the species being studied is not mentioned in the title or abstract of many articles. Consequently, such data are not easily accessible in the PubMed database. These omissions can mislead readers about the true nature of developmental processes and delay the acceptance of valid species differences. To improve the accuracy of the scientific record, I suggest that journals should require that authors include the name of the speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…They demonstrate that nearly a third of all papers fail to note the number of animals used. Similarly, BarbaraMigeon (2014) found that in more than 1000 biology research articles collected between 2012 and 2014, the animal species is not mentioned in the title 61% of the time, (if not in the title) in the abstract 35% of the time, or at all 23% of the time 3. For more on the ethics of care approach and the role of aesthetics, see Josephine Donovan's The Aesthetics of Care: On the Literary Treatment ofAnimals, Bloomsbury, 2016.…”
mentioning
confidence: 99%
“…They demonstrate that nearly a third of all papers fail to note the number of animals used. Similarly, BarbaraMigeon (2014) found that in more than 1000 biology research articles collected between 2012 and 2014, the animal species is not mentioned in the title 61% of the time, (if not in the title) in the abstract 35% of the time, or at all 23% of the time 3. For more on the ethics of care approach and the role of aesthetics, see Josephine Donovan's The Aesthetics of Care: On the Literary Treatment ofAnimals, Bloomsbury, 2016.…”
mentioning
confidence: 99%